Psychotherapy in Hungary during the Socialist Era and the Socialist Dictatorship - Buda, Béla; Tomcsányi, Teodóra; Harmatta, János; Csáky-Pallavicini, Roger; Paneth, Gábor (European Journal of Mental Health, 2009)
This study provides an overview of how psychotherapy’s Hungarian representatives tried to safeguard and transmit psychotherapeutic training and practice during the time of socialist dictatorship. At first, even some Soviet ideologists had considered psychoanalysis to be compatible with Marxist ideology. However, over the course of a few years, socialist ideology exerted pressure on psychotherapy’s theory, training, and therapeutic practice. This was done initially on an ideological level, but later it increasingly resorted to physical violence as well, both there and through its export to a Hungary occupied by the Soviet army. All this was similar to its stand against the arts and literature. The first thing to appear as a result of this was a denial of the necessity of psychotherapy (stating that psychotherapy was only needed because of ‘capitalist market conditions’, with even the teaching of psychology being nearly stopped); later anyone could face serious repercussions for belonging to any school of psychotherapy, especially the analytic. It was also a part of the arsenal of those in power to put crucial centres of therapy decisively under the leadership of appropriately aligned neurophysiologists for long periods of time. The state kept these under strict control, and healing was reduced to medication procedures. The authors provide examples of the modest internal and external opportunities that nevertheless arose for prominent representatives of psychotherapy to solve these dilemmas. With the weakening of the dictatorship, the war on psychotherapy also subsided in a relative and inconsistent way. At this point, events in the politics of science were characterised by the degree of loyalty to the Soviet association, who were visibly abusing psychiatry, and the fight to preserve the relative independence of this field of science. The final part of the study touches upon one or two dilemmas of the heroic age of starting over that surfaced at the time of the political system’s change.